2017
DOI: 10.1007/s10096-017-3000-1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pre-enrichment for detection of third-generation cephalosporin-resistant Enterobacteriaceae (3GCREB) from rectal swabs

Abstract: Screening for multidrug-resistant Enterobacteriaceae is performed in many institutions as part of infection control measures. However, the sensitivity of current standard diagnostics is modest. Furthermore, patients are usually screened by rectal swabs (mostly rayon based), which have been shown to be sub-optimal for the recovery of Enterobacteriaceae. Therefore, it is likely that many patients colonised with multidrug-resistant Enterobacteriaceae remain undetected. The present study aimed to analyse if the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…Es ist schwer, aus solchen Zusammenstellungen einen epidemiologischen Zusammenhang herauszufinden. [12]. Darüber hinaus sollten breite Screeningmaßnahmen zur Surveillance in der endemischen Situation kritisch betrachtet werden, da sowohl für den individuellen Patienten als auch für die Allgemeinheit der Nutzen einer solchen mikrobiologischen Diagnostik ohne Infektionsverdacht fraglich ist [13].…”
unclassified
“…Es ist schwer, aus solchen Zusammenstellungen einen epidemiologischen Zusammenhang herauszufinden. [12]. Darüber hinaus sollten breite Screeningmaßnahmen zur Surveillance in der endemischen Situation kritisch betrachtet werden, da sowohl für den individuellen Patienten als auch für die Allgemeinheit der Nutzen einer solchen mikrobiologischen Diagnostik ohne Infektionsverdacht fraglich ist [13].…”
unclassified
“…As the systematic microbiological screening was not continued or repeated after reinforcing the IC measures, we cannot be sure if the outbreak had really ended. There might have been undetected cases because the direct plating of rectal swabs has a low sensitivity of detection [31]. In addition, we did not have any cases of non-ESBL KPN during the same period, and therefore we could not perform a risk analysis.…”
Section: Discussionmentioning
confidence: 96%
“…This pre-enrichment step was included to mimic our laboratory algorithm for screening of multiresistant Enterobacterales in rectal samples. Former studies on the screening of third generation cephalosporin resistance have shown that a pre-enrichment strategy results in higher yield compared to direct plating (2830). We assume that that the use of a pre-enrichment strategy in clinical setting will result in a similar detection range, though inoculum of the original sample may differ.…”
Section: Discussionmentioning
confidence: 99%